The Prevalence of Risk Factors for Coronary Artery Disease in Post Coronary Artery Bypass Graft Patients (KYAMC Journal, 2020)
Background: Cardiovascular diseases, the part of non communicable diseases are the 30% death in Bangladesh. Many patients undergoing coronary artery bypass graft surgery have previous cardiovascular risk factors which could be prevented.Objectives: To assess the prevalence of cardiovascular risk factors in the patients undergoing coronary artery bypass graft surgery.Materials and Methods: All patients who had coronary artery bypass grafting between January 2018 to June 2018 data were collected retrospectively in six month duration time at a tertiary cardiac care hospital in Dhaka, Bangladesh. The prevalence rate of conventional risk factors are presented for observational study.Results: Out of 305 patients, 251 (82.3%) were male and 54 (17.7%) were female. The age ranged from 31 to 78 years old. The mean age was(56.72 ± 3.6). Hypertension was present in 249 (81.6% ),diabetes 211 (69.2%), Dyslipidemia had 200 ( 65.6% ), smoking habits had 105 (34.4%) and strong family history 9 (3%). As far as the obesity was concern 149 (48.9%)normal weight,128 (42.0%) patients were overweight and 25(8.2%) were obese. Majority of the patients had 3 risk factors together 136(44.6%), 2 risk factors 82 (26.9%), 1 risk factor 41(13.4%), 4 risk factors 38(12.5%) and 8(2.6%) had no risk factors. As compared to using the bypass technique there were 242(79.4%) On pump arrest heart, 40(13.1%) by On pump beating and 23(7.5%) were by Off pump beating. Mortality was 2.3%.Out of them 3(42.86%) patients had 3 risk factors, 2 (28.57%) patients had 2 risk factors and 2(28.57%) patients had 1 risk factor.Conclusion: The most common risk factors were hypertension, followed by diabetes, dyslipidemia , male gender, smoking, obesity and positive family history. These patients are recommended to be trained regarding lifestyle changes. Also, prevention strategies can play an important role in reducing patients' morbidity and mortality.KYAMC Journal Vol. 11, No.-1, April 2020, Page 9-13